The IMPACT OF SUPPLY CHAIN DIGITALIZATION ON SUPPLY CHAIN RESILIENCE AND PERFORMANCE - Kisu Candra, Brandon; Laulita, Nasar Buntu (Management Department, Faculty of Economics and Business, Universitas Jambi, 2025)
In the recent era after the COVID-19 pandemic has ended, many companies, both large and small, are still experiencing difficulties caused by increasing inflation in shipping and import costs. As a result, companies experience a drastic decline in demand levels that can lead to losses and damage to the supply chain system. To be able to address these problems, companies must be able to innovate in the use of digital technology in an effort to achieve better supply chain performance so as to be able to mitigate price inflation and also reduce the risk of potential problems. Data collection was gathered with the help of questionnaires which targeted at industrial companies that involve supply chain systems in their operations. The results of the collected data and later analysis show that use of digital technology has a big effect on resilience and performance of the supply chains system, thus having a positive impact for the company. This research is anticipated to serve useful for other researchers as a concrete data source to determine the impact it brings on a company's performance.